Analysis Of Competition Level Factors Of Clinical Practices In Vk Institute Use Of Personal Protective Equipment (Ppe) In Wide Care Post Op Section Cesarea (SC) In Sidoarjo Hospital - Al Firdausi, Chilma; Mayasari, Ema; Yudhana, Amarin (Journal of Global Research in Public Health, 2019)
The use of PPE should be carried out by health officers and students of clinical practice. The general objective of this research is to analyze the factors that influence the compliance of clinical practice students in using personal protective equipment of PPE In Wide Care Post Op Section Cesarea (SC) In Sidoarjo Hospital. The design of this research is quantitative with cross sectional approach. The population of this study is all students clinical practice in the VK (Verlos Kamer) room in Sidaorjo Hospital. The sample size is 27 respondents taken by Total Sampling technique. Variable dependent compliance student clinical practice, independent variable knowledge, experience, organization policy. The result of analysis using logistic regression. The result of the research shows that the respondents have high knowledge that is 19 respondents (70,4%), the respondents have experience of wound care that is 18 respondent (66,7%), the respondent do organizational policy that is 18 responden (66,7%), do wound care using PPE (personal protective equipment) that is 19 respondents (70,4%). Result of data analysis got p value = 0,000 <(0,05), which means that there is correlation between knowledge with level of compliance of clinical practice student in Sidoarjo Hospital. Result of data analysis got result p value = 0,037 <(0,05), meaning that there is relation between organization policy with level of compliance of clinical practice student in Sidoarjo Hospital. Knowledge is very influential on the behavior of students in using PPE (personal protective equipment). A person's behavior will be better and can last longer if based on good knowledge and awareness. As a Facilitator a clinical counselor is able to facilitate the student and as an evaluator able to evaluate whether the achievement of the student has been in accordance with the determined competency